2022
DOI: 10.1007/s00344-022-10665-7
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin B1-Induced Oxidative Burst Perturbed Photosynthetic Activity and Affected Antioxidant Enzymatic Response in Tomato Plants in Ethylene-Dependent Manner

Abstract: Fumonisin B1 (FB1) is a harmful mycotoxin produced by Fusarium species, which results in oxidative stress leading to cell death in plants. FB1 perturbs the metabolism of sphingolipids and causes growth and yield reduction. This study was conducted to assess the role of ethylene in the production and metabolism of reactive oxygen species in the leaves of wild type (WT) and ethylene receptor mutant Never ripe (Nr) tomato and to elucidate the FB1-induced phytotoxic effects on the photosynthetic activity and antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Beyond cereals and Arabidopsis, more recent studies on fruits such as tomatoes and bananas have also increased our understanding of the cellular impacts of FB1. A study on tomatoes determined that ethylene plays an important role in the regulation of FB1-mediated cell death and defence activation, significantly affecting photosystems I and II and activating photoprotective mechanisms [ 28 ]. In bananas, FB1 biosynthesis by F. proliferatum contributed to fungal infection by decreasing plant defence, enhancing oxidative stress and ROS production, regulating energy metabolism and accelerating cell death [ 29 , 30 ].…”
Section: Cellular Effects Of Trichothecenes and Fumonisins On Cerealsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond cereals and Arabidopsis, more recent studies on fruits such as tomatoes and bananas have also increased our understanding of the cellular impacts of FB1. A study on tomatoes determined that ethylene plays an important role in the regulation of FB1-mediated cell death and defence activation, significantly affecting photosystems I and II and activating photoprotective mechanisms [ 28 ]. In bananas, FB1 biosynthesis by F. proliferatum contributed to fungal infection by decreasing plant defence, enhancing oxidative stress and ROS production, regulating energy metabolism and accelerating cell death [ 29 , 30 ].…”
Section: Cellular Effects Of Trichothecenes and Fumonisins On Cerealsmentioning
confidence: 99%
“…Ethylene signalling is an important factor in sphingolipid synthesis, and it has been shown to partially rescue FB1-induced cell death in tomatoes in Arabidopsis [ 28 , 52 ]. Relatively few studies have elucidated maize mechanisms that confer tolerance to fumonisins.…”
Section: Plant Resistance To Trichothecenes and Fumonisinsmentioning
confidence: 99%
“…OH), and singlet oxygen ( 1 O 2 ) [15]. These antioxidants include superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), polyphenol oxidase (PPO), ascorbate peroxidase (APX), ascorbate (ASA), and glutathione (GSH) and perform scavenging function of ROS production during pathogenic attacks [17,26].…”
Section: Plant Antioxidant System To Combat Fungal Pathogensmentioning
confidence: 99%
“…In addition, cell death plays an essential role in the coordination of plant growth and development, as well as in the induction of cellular responses to various stresses (Valandro et al 2020 ). Plants induce cell death at the infection site to prevent further spread of pathogen infection and toxin production (Iqbal et al 2022 ; Xing et al 2013 ). Saffron root tip cells were exposed to 25–200 µM FA for 60 h, and it was observed that FA induced higher H 2 O 2 accumulation, chromatin condensation and DNA breakage followed by cell death (Samadi and Shahsavan Behboodi 2006 ).…”
Section: Fa-induced Dna Fragmentation and Genotoxicitymentioning
confidence: 99%